BRAFV600E augments WNT signaling in colorectal cancer via aberrant DNA methylation - Layla El Bouazzaoui; Jeroen M. Bugter; Emre Küçükköse; André Verheem; Jasmin B. Post; Nicola Fenderico; Inne H.M. Borel Rinkes; Hugo J.G. Snippert; Madelon M. Maurice; Onno Kranenburg (iScience)
Summary: The BRAFV600E mutation drives an aggressive subtype of colorectal cancer (CRC). Although WNT signaling activation is a hallmark of CRC, APC mutations are uncommon in BRAF-V600E mutant CRC, and RNF43 mutations are instead suspected to drive WNT pathway activation. Here, we investigated WNT pathway activation in BRAF-V600E mutant CRC using CRISPR-LbCpf1-corrected BRAF (V600E) and RNF43 (P441fs) organoids. BRAFE600V organoids regained dependency on EGF receptor signaling, and lost tumorigenic potential. Under identical growth conditions, correction of BRAFV600E, rather than RNF43P441fs, suppressed WNT target genes and upregulated epithelial differentiation genes and WNT antagonist genes. DNA methylation analysis revealed promoter hypermethylation of WNT antagonist genes and gene body hypermethylation —associated with transcriptional upregulation— of key WNT effectors (LGR5, EPHB2, and TCF4) in BRAFV600E organoids. Demethylation treatment resulted in upregulation of WNT antagonists and reduced WNT target gene expression in BRAFV600E organoids. Our results demonstrate that BRAFV600E enhances WNT pathway activation through modulation of DNA methylation patterns.